Neurosurgical tactile discrimination training with haptic-based virtual reality simulation. (December 2014) - Patel, Achal; Koshy, Nick; Ortega-Barnett, Juan; Chan, Hoi C.; Kuo, Yong-Fan; Luciano, Cristian; Rizzi, Silvio; Matulyauskas, Martin; Kania, Patrick; Banerjee, Pat; Gasco, Jaime
<x content-type="archive" xml:space="preserve">Abstract</x> Objective: To determine if a computer-based simulation with haptic technology can help surgical trainees improve tactile discrimination using surgical instruments. Material and Methods: Twenty junior medical students participated in the study and were randomized into two groups. Subjects in Group A participated in virtual simulation training using the ImmersiveTouch simulator (ImmersiveTouch, Inc., Chicago, IL, USA) that required differentiating the firmness of virtual spheres using tactile and kinesthetic sensation via haptic technology. Subjects in Group B did not undergo any training. With their visual fields obscured, subjects in both groups were then evaluated on their ability to use the suction and bipolar instruments to find six elastothane objects with areas ranging from 1·5 to 3·5 cm2 embedded in a urethane foam brain cavity model while relying on tactile and kinesthetic sensation only. Results: A total of 73·3% of the subjects in Group A (simulation training) were able to find the brain cavity objects in comparison to 53·3% of the subjects in Group B (no training) (P = 0·0183). There was a statistically significant difference in the total number of Group A subjects able to find smaller brain cavity objects (size ≤ 2·5 cm2) compared to that in Group B (72·5 vs 40%, P = 0·0032). On the other hand, no significant difference in the number of subjects able to detect larger objects (size ≧ 3 cm2) was found between Groups A and B (75 vs 80%, P = 0·7747). Conclusion: Virtual computer-based simulators with integrated haptic technology may improve tactile discrimination required for microsurgical technique.